Effects of ethylene, simulated transport duration and maturity stage on postharvest quality characteristics of vapour heat-treated Carica papaya L. - Hasan, Fatimahtul Hazwani (2014)
The papaya industry is rejuvenated with the introduction of the new F1 hybrid variety called ‘Frangi’ or commercially known as ‘Paiola’ (Carica papaya L.). Currently, the production of papaya has become more prominent in Malaysia due to the high demand in the domestic market, and also for export mainly to China and Japan. However, fruit fly infestation has become a serious problem, especially when the papaya fruit peel has turned 25% yellow. Thus, China and Japan have made the vapour heat treatment (VHT) as an export requirement for disinfestation of fruit flies in Malaysia. China and Japan require the exporting country to carry out ripening treatments of papaya before export so that when the fruits arrived at the destination, the fruits are ripe and ready for market. Thus, the fruits need to be ripened with ethylene gas before shipment in order to make the fruit ripened uniformly when they reach the target market. The best storage temperature for papaya was 12 °C and shipping condition for papaya is 13 °C for 8 day transport duration. The first objective was to determine the effects of ethylene treatments and maturity stages 4, 5 and 6 on quality characteristics of vapour-heat treated papaya during storage at 25 ˚C for local market distribution. The second objective of this study was to determine the effect of ethylene treatment and simulated transport duration at 13 °C at maturity stages 4, 5 and 6 on quality characteristics of vapour-heat treated papaya. Fruits were arranged and loaded into the VHT chamber. The VHT system was turned on. The temperatures of the chamber and fruit core were raised to 48 °C and 46.5 ˚C respectively. The respective temperatures were maintained for 20 min, followed by air and water cooling at 35 and 10 min, respectively. Then fruits were dried for 5 min and removed from the VHT system and repacked. After VHT, the fruits were treated with 100 μL.L-1 ethylene gas at 20 ˚C for 24 hours. Non-ethylene treated (control) fruits were kept separately at 20 ˚C for 24 hours. After 24 hours, the fruits were removed from the ripening rooms, and stored at 25 ˚C and 13 ˚C, for the first and second experiment, respectively. Measurements for ripening characteristics of fruits that reached maturity stages 4, 5, and 6, were made. The characteristics measured were peel and pulp colour, firmness, soluble solids concentration, titratable acidity ascorbic acid and pH, and ethylene and carbon dioxide production. The first study was carried out in a factorial experiment of 2 levels of ethylene (with and without ethylene) × 3 maturity stages (4, 5 and 6), with three replications. The second experiment was carried out in a factorial experiment of 2 levels of ethylene (with and without ethylene) × 4 storage durations (2, 4, 6 and 8) × 3 maturity stages (4, 5 and 6), with three replications. For the first experiment, the fruits ripened normally at 25 °C with or without ethylene following VHT with respect to peel and pulp colour, edible firmness and soluble solids concentration. The fruits at maturity stage 5 were the edible stage by considering the firmness, soluble solids concentration, and titratable acidity, and ascorbic acid contents. The titratable acidity and ascorbic acid contents were found to increase with increasing maturity in response to heat treatment. The productions of ethylene and carbon dioxide were adequate to stimulate normal ripening processes as the fruits ripened from maturity stage 4 to 6. It is can be recommended that no ethylene treatment is needed to ripen fruits that had been treated with VHT, since the ethylene treatment did not affect the ripening process of the fruits. For second experiment, the responses of the physical, chemical and physiological characteristics of fruits showed that the vapour-heat treated fruits were able to ripen normally during the simulated transport at 13 °C. The fruit peel and pulp achieved the full ripe colour of vivid orange. The fruit firmness treated with and without ethylene decreased with increasing fruit maturity. However, the pulp of ethylene treated fruits was palatable at maturity stage 5 as it decreased to a desirable firmness. Variable effects of these quality characteristics of the papaya that were observed between the ethylene treatments and simulated transport duration, could be due to the exposure of the fruits to vapour-heat followed by the simulated storage at 13 °C. Application of exogenous ethylene on fruits is most common used method to stimulate rapid and uniform ripening. However, the vapour-heat treated fruits were not responsive to ethylene treatment during simulated transport at 13 °C. Further investigations need to be conducted to determine the optimum stage of maturity and transport temperature of vapour-heat treated papaya in order for the fruits to reach the market at a palatable stage.